Penggunaan The Socratic Method untuk Meningkatkan Critical Thinking Skill Siswa Kelas 7 SMP-IT Syaikhuna Zainuddin Atsani NW Lingkuk Dane - Yuliani, Yuliani; Junaidin, Junaidin; Sukuryadi , Sukuryadi (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study aims to analyze the effectiveness of the use of the Socratic Method in improving Critical Thinking Skills. The Socratic Method, which focuses on in-depth and collaborative dialogic interactions between teachers and students, motivates students to be active in exploring, testing beliefs, and critically analyzing information. Various studies have shown that the application of this method, especially in mathematics education at the junior and senior high school levels, can significantly improve students' Critical Thinking Skills compared to traditional teaching methods. Findings from the study at SMPN showed that more than 75% of students were actively and effectively involved in the learning process, with a consistent increase in critical thinking scores in the aspects of clarification, investigation of assumptions, reasons, evidence, and reflection. The Socratic Method has also proven successful in improving students' ability to make decisions based on independent analysis and logical arguments, making it very relevant to be implemented in today's educational context that requires the development of high-level thinking skills. Other studies have also shown that the Socratic Dialogue approach has a significant success rate in improving students' Critical Thinking Skills. Thus, this approach is highly recommended for adoption in the educational process.